Nitrogen compounds prevent H9c2 myoblast oxidative stress-induced mitochondrial dysfunction and cell death - Silva, João P. (2010)
Oxidative stress has been connected to various forms of cardiovascular diseases. Previously, we have been investigating the potential of new nitrogen-containing synthetic compounds using a neuronal cell model and different oxidative stress conditions in order to elucidate their potential to ameliorate neurodegenerative diseases. Here, we intended to extend these initial studies and investigate the protective role of four of those new synthetic compounds (FMA4, FMA7, FMA762 and FMA796) against oxidative damage induced to H9c2 cardiomyoblasts by tert-butylhydroperoxide (t-BHP). The data indicates that FMA762 and FMA796 decrease t-BHP-induced cell death, as measured by both sulforhodamine B assay and nuclear chromatin condensation evaluation, at non-toxic concentrations. In addition, the two mentioned compounds inhibit intracellular signalling mechanisms leading to apoptotic cell death, namely those mediated by mitochondria, which was confirmed by their ability to overcome t-BHP-induced morphological changes in the mitochondrial network, loss of mitochondrial membrane potential, increased expression of the pro-apoptotic proteins p53, Bax and AIF and activation of caspases-3 and -9. Importantly, our results indicate that the compounds’ ROS scavenging ability plays a crucial role in the protection profile, as a significant decrease in t-BHP-induced oxidative stress occurred in their presence. Data obtained indicates that some of the test compounds may clearly prove valuable in a clinical context by diminishing cardiac injury associated to oxidative stress without any toxicity.